Cross‐Sectional Evidence for a Stress‐Negative Affect Pathway to Substance Use among Sexual Minority Girls. Issue 4 (19th April 2013) - Marshal, Michael P.; Burton, Chad M.; Chisolm, Deena J.; Sucato, Gina S.; Friedman, Mark S.
Abstract: Sexual minority girls (SMGs) are four times more likely to engage in substance use than are heterosexual girls. A better understanding of the explanatory mechanisms of this disparity is needed to inform prevention and intervention programs. The goal of this study was to conduct a preliminary test of a "stress‐negative affect" pathway by examining gay‐related victimization and depression as mediators of substance use among SMGs. Adolescent girls ( N = 156, 41% SMGs) were recruited from two urban adolescent medicine clinics to participate in an NIH‐funded study of adolescent substance use. The average age was 17.0 years old and 57% were nonwhite. Mediation analyses were conducted in a multiple regression framework using SPSS and a mediation macro utilizing bias‐corrected bootstrapping. Four models were estimated to test mediated pathways from sexual orientation to gay‐related victimization (Mediator 1), to depression symptoms (Mediator 2), and then to each of four substance use variables: cigarettes, marijuana, alcohol, and heavy alcohol use. Significant mediated pathways (mediation tests with 95% CIs) were found for cigarette, alcohol and heavy alcohol use outcome variables. Results provide preliminary support for the minority stress hypothesis and the stress‐negative affect pathway, and may inform the development of future prevention and intervention programs.